Narratives and evidence: struggles over Mohamed Mahmoud - Hazzaa, Manar (AUC Knowledge Fountain, 2016)
This research focused on the construction of competing narratives of the events of November 2011 in Mohamed Mahmoud Street, popularly named as the Mohamed Mahmoud events. Since the making, naming and categorization of the "event" has not been limited to the happenings of November 2011, my research thus asked how is an event made into a narrative, what are its temporal boundaries, and what evidence is used to construct it as an event and as a historical narrative that is recognized. Since each narrative/story is presented with its own evidence; I analyzed the production of different stories by different participants, how they construct the event, and how they use evidence to render their construction more credible, authoritative, and legitimate in relationship to others. The research addressed some key questions such as: who is telling what stories about what happened, in which way, using what kind of evidence. Additionally I ask how these different stories construct an event as a recognizable event and how the construction of this event by itself produces evidence.